Non-melanoma skin cancer treated with high-dose-rate brachytherapy: a review of literature - Delishaj, Durim; Rembielak, Agata; Manfredi, Bruno; Ursino, Stefano; Pasqualetti, Francesco; Laliscia, Concetta; Orlandi, Francesca; Morganti, Riccardo; Fabrini, Maria Grazia; Paiar, Fabiola (Journal of Contemporary Brachytherapy, 2016)
Purpose: The incidence of non-melanoma skin cancer (NMSC) has been increasing over the past 30 years. There are different treatment options and surgical excision is the most frequent treatment due to its low rates of recurrence. Radiotherapy is an effective alternative of surgery, and brachytherapy (BT) might be a better therapeutic option due to high radiation dose concentration to the tumor with rapid dose fall-off resulting in normal tissues sparing. The aim of this review was to evaluate the local control, toxicity, and cosmetic outcomes in NMSC treated with high-dose-rate BT (HDR-BT). Material and methods: In May 2016, a systematic search of bibliographic database of PubMed, Web of Science, Scopus, and Cochrane Library with a combination of key words of “skin cancer”, “high dose rate brachytherapy”, “squamous cell carcinoma”, “basal cell carcinoma”, and “non melanoma skin cancer“ was performed. In this systematic review, we included randomized trials, non-randomized trials, prospective and retrospective studies in patients affected by NMSC treated with HDR-BT. Results: Our searches generated a total of 85 results, and through a process of screening, 10 publications were selected for the review. Brachytherapy was well tolerated with acceptable toxicity and high local control rates (median: 97%). Cosmetic outcome was reported in seven study and consisted in an excellent and good cosmetic results in 94.8% of cases. Conclusions : Based on the review data, we can conclude that the treatment of NMSC with HDR-BT is effective with excellent and good cosmetics results, even in elderly patients. The hypofractionated course appears effective with very good local disease control. More data with large-scale randomized controlled trials are needed to assess the efficacy and safety of brachytherapy.